MARKETING OF COFFEE IN RWANDA – COSTS AND CHALLENGES - SEEMA, FIDELE KABAYIZA, P. RADHIKA and (The Journal of Research, PJTSAU, 2019)
Rwanda is a landlocked country situated in Central Africa. Also known as the land of a thousand hills, Rwanda has five volcanoes, twenty-three lakes and numerous rivers, some forming the source of the River Nile. The country lies 75 miles South of the equator in the Tropic of Capricorn, 880 miles West of the Indian ocean and 1,250 miles East of the Atlantic ocean - literally in the heart of Africa. Coffee production in Rwanda dates back to 1904 with its first export occurring in 1917 (USAID, 2006). Since its introduction into Rwanda, coffee has played an important role in the economic development of the country and coffee growing is mainly a smallholder’s activity. For many years, coffee has been the major source of foreign currency in Rwanda (MINAGRI, 2010).